Clinical Outcomes among Patients with Active Cancer and Acute Ischemic Stroke Treated with Antiplatelet versus Anticoagulant Therapy. - Gianluca Costamagna; Andreas Hottinger; Francoise Livio; Babak Benjamin Navi; Davide Strambo; Patrik Michel (International Journal of Stroke, 2026)
Background: Patients with acute ischemic stroke (AIS) and active cancer (AC) face high risks of recurrent stroke and death. Evidence guiding antithrombotic selection remains limited. Aims: To investigate post-AIS prescribing patterns of antiplatelet versus anticoagulant therapy in AIS patients with AC and their associated clinical characteristics and outcomes. Methods: We retrospectively analyzed 2003–2024 data from the Acute-Stroke-Registry-and-Analysis-of-Lausanne (ASTRAL). We included patients with AC discharged after index AIS on antiplatelet therapy (single or dual) or anticoagulation (±antiplatelet therapy). We excluded patients with no or inactive cancer, missing data on discharge antithrombotics, cancer diagnosed after hospitalization, and those who died or entered palliative care before treatment decisions. The primary outcome was a recurrent ischemic cerebrovascular event within 12 months. Secondary outcomes included 3-month ischemic cerebrovascular recurrence, modified Rankin Scale (mRS) shift and all-cause mortality. The safety outcome was symptomatic intracranial hemorrhage (ICH) at 3 and 12 months. We used multivariable regression models adjusted for prognostic variables. Results: Among 8,035 patients with AIS, 313 had AC and met eligibility criteria. Median age was 73 years (IQR 63–79), and 111 (35%) were women. At discharge, 178 (57%) received antiplatelet therapy and 135 (43%) anticoagulation. Patients previously naïve to antithrombotic therapy (n=150) more often received antiplatelet therapy (68% vs 32%, p